2009
DOI: 10.1590/s0034-71672009000200012
|View full text |Cite
|
Sign up to set email alerts
|

A vivência do cuidador familiar de vítima de Acidente Vascular Encefálico: uma abordagem interacionista

Abstract: This qualitative research aimed at understanding the experience of familiar caregivers in the process of caring for persons disabled by stroke, in their home. It was held in the Program of Domiciliary Assistance of a tertiary public hospital in Fortaleza-CE, with nine caregivers. The statements were obtained through interviews recorded and organized into categories, then interpreted according to the Symbolic Interactionism method: why I take care?, Realizing the family victimized by stroke, the daily activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
26

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 5 publications
1
9
0
26
Order By: Relevance
“…Os cuidadores subdividiram em AVDs a alimentação, integridade da pele, higiene, eliminações, terapêutica, locomoção e movimentação do paciente, e atividades instrumentais como preparar refeições, lavar e passar roupas, limpar a casa e realizar tarefas extradomiciliares (10,11) .…”
Section: Introductionunclassified
“…Os cuidadores subdividiram em AVDs a alimentação, integridade da pele, higiene, eliminações, terapêutica, locomoção e movimentação do paciente, e atividades instrumentais como preparar refeições, lavar e passar roupas, limpar a casa e realizar tarefas extradomiciliares (10,11) .…”
Section: Introductionunclassified
“…Individuals who suffer a stroke become vulnerable and are exposed to situations that change the way they see themselves and construct their identities (17) . In the case of the study subjects, some individuals showed themselves to be active and independent people, whereas others were engaged in the full productive phase of life and assumed responsibility to provide for their families, theses activities maintained the sense of self.…”
Section: Discussionmentioning
confidence: 99%
“…The perception of the negative aspects related to the stroke, characterized by the fear of death and of the sequelae, demonstrates that the meaning attributed to the disease refers to a life-threatening situation. This development interferes in the coping process (6,17) , which consists of the activity of human beings to act in accordance with what they encounter in their lives, with their actions constructed by the ways they perceive, evaluate, and interpret salient details and by the type of projected courses of action they plan.…”
Section: Discussionmentioning
confidence: 99%
“…Para isso devem estabelecer com a mulher um espaço educativo, no qual sejam instrumentalizadas para seu cuidado e do recém-nascido. Nessa perspectiva, o profissional deve introduzir em seu cuidado instrumentos que facilitem o processo de adaptação da mulher à nova situação, promovendo sua capacitação para o cuidado à criança 10 . Os dados foram coletados por meio de entrevista semiestruturada individual.…”
Section: Revisão De Literaturaunclassified